2019
DOI: 10.1159/000494920
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal Symptoms in Inflammatory Bowel Disease Are Correlated with Gastric Emptying and Serum Levels of Active Ghrelin

Abstract: Background: Inflammatory bowel disease (IBD) is associated with delay in gastric emptying, increase in ghrelin, and decrease in leptin. The aim was to investigate the correlation between gastroduodenal (GD) symptoms, gastric emptying, and serum levels of active ghrelin and leptin in IBD. Twenty-seven IBD patients and 26 healthy volunteers were asked to complete the Porto Alegre Dyspeptic Symptoms Questionnaire. A gastric emptying test for solids was performed using a C13 octanoic acid breath test. During this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This study identified a prevalence of 52.7% H. pylori infection in patients with dyspepsia attending a public health clinic that provides care primarily to low-income people of the same ethnic origin. These data are similar to infection rates observed in less-developed economies of the world (Kotilea et al, 2019) and differ from the prevalence rates found in southern and south-eastern Brazil, which are areas with the best socioeconomic and healthcare conditions in the country (Sales et al, 2019; Toscano et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study identified a prevalence of 52.7% H. pylori infection in patients with dyspepsia attending a public health clinic that provides care primarily to low-income people of the same ethnic origin. These data are similar to infection rates observed in less-developed economies of the world (Kotilea et al, 2019) and differ from the prevalence rates found in southern and south-eastern Brazil, which are areas with the best socioeconomic and healthcare conditions in the country (Sales et al, 2019; Toscano et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…There are relevant differences in the prevalence of H. pylori infection within Brazil. Rates vary from 82% in the northern cities (Reis Júnior et al, 2012), 79% in the northeast (Barbosa et al, 2018), 35% in the southwest (Toscano et al, 2018), and 30% in the south (Sales et al, 2019). These differences probably reflect the different levels of urbanization, sanitation, access to clean water, and community socioeconomic status in these regions (Hooi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high serum levels of ghrelin have been reported in patients with inflammatory bowel diseases and experimental colitis 104 . Some researchers confirm that the upregulation of ghrelin is an attempt to counter tissue damage following intestinal inflammation; damage may stimulate the secretion of endogenous ghrelin 105 .…”
Section: Ghrelin Regulates Inflammation In Gastrointestinal Diseasesmentioning
confidence: 98%
“…In addition, high serum levels of ghrelin have been reported in patients with inflammatory bowel diseases and experimental colitis. 104 Some researchers confirm that the upregulation of ghrelin is an attempt to counter tissue damage following intestinal inflammation; damage may stimulate the secretion of endogenous ghrelin. 105 Coincidentally, a prospective clinical study in China demonstrated that serum ghrelin was negatively associated with esophageal and gastric cancer, implying the potential role of ghrelin as a marker of gastric mucosal alterations in upper gastrointestinal cancers.…”
Section: Inflammation In Gastrointestinal Diseasesmentioning
confidence: 99%
“…Ghrelin attenuates leptin-induced proinflammatory responses in macrophages and T cells, causing a reduction in the concentration of proinflammatory cytokines (including TNF-α, IL-1, IL-6, and IL-8) and lowering the secretion of leptin in the gastrointestinal tract [ 159 ]. Expression of ghrelin in the course of IBD turned out to be significantly higher in comparison to the controls [ 160 , 161 ]. In a model of TNBS-induced murine colitis, intraperitoneal administration of exogenous ghrelin improved the general outcome without an impact on PPAR-γ expression [ 162 ].…”
Section: Other Adipokinesmentioning
confidence: 99%